Desire in Language / A Semiotic Approach to Literature and Art - Roudiez Leon S (Columbia University Press, 1980)
Preface, Acknowledgements, Introduction by Leon S. Roudiez, The Ethics of Linguistics, The Bounded Text, Word and Dialogue and Novel, How does One Speak to Literature, From One Identity to an Other, The Father and Love and Banishment, The Novel as Polylogue, Giotto's Joy, Motherhood According to Giovsnni Bellini, Place Names, Index.
Preface, Acknowledgements, Introduction by Leon S. Roudiez, The Ethics of Linguistics, The Bounded Text, Word and Dialogue and Novel, How does One Speak to Literature, From One Identity to an Other, The Father and Love and Banishment, The Novel as Polylogue, Giotto's Joy, Motherhood According to Giovsnni Bellini, Place Names, Index.